Дослідження терапевтичних властивостей нових низькомолекулярних органічних сполук на моделях виразкоутворення у щурів - Маркевич, Анна; Вірченко, Олександр; Фалалєєва, Тетяна; Кудрявцев, Костянтин; Берегова, Тетяна; Markevich, Anna; Virchenko, Oleksandr; Falalyeyeva, Tetiana; Kudryavtsev, Kostyantyn; Beregova, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2014)
На 224 щурах проведений скринінг синтезованих органічних сполук щодо їх ефективності в лікуванні виразок. Показано, що пролінвмісна сполука КУД 259 здійснювала найбільший терапевтичний вплив на ураження в шлунку щурів за усіх моделей експериментального виразкоутворення (стресова, етанолова, індометацинова й аспіринова моделі).

The aim was to study the effect of therapeutic administration of novel low molecular weight organic compounds on rat gastric ulcer caused by stress, ethanol, non-steroidal anti-inflammatory drugs (indomethacin and aspirin). Work was carried out on 224 white laboratory rats, divided into 8 groups in each of four ulcer models. The first two groups were injected intraperitoneally with 2 ml/kg of physiological saline and 1 % DMSO respectively for 3 days after ulcerogenic stimulus. Groups 3-8 were treated with compounds KUD 142, 259, 284, 772, 837, 796 at a dose of 1 mg/kg. It was found that a low molecular weight organic compound KUD 259 dissolved in DMSO has the strongest therapeutic effects in all models of ulcer formation. In the chemical structure of the substance proline and phenolic groups are effectively combined. Gastroprotective, antioxidant and antisecretory action of proline peptides and polyphenols has been discovered. Antiulcer properties of the studied substance KUD259 were more pronounced, that may be due to the presence of the two functional groups in its structure.
The Study of Therapeutic Properties of New Low Molecular Weight Organic Compounds on Rat Ulcer Models.
Keywords: пролінвмісна органічна сполука; виразка шлунка.; proline containing organic compound; gastric ulcer